Compact stars:nuclear physics, particle phyiscs and general relativity - Glendenning, Norman K. (New York, Springer Verlag, 1997)
Neutron stars are the smallest dense stars known, with densities some 1014 times that of Earth. This text discusses the physics of these extreme objects and includes the needed background in classical general relativity in nuclear and particle physics.
Appendix A 362p.; Bibliographical References 365-381p.; Index 383-390p.
Keywords: General relativity; Neutron stars; White dwarf; Generalia